Paleobiogeography of Africa: How distinct from Gondwana and Laurasia? - (:unkn) unknown (My University, 2006)
Although Africa was south of the Tethys Sea and originally belonged to the Gondwana, its paleobiogeographical history appears to have been distinct from those of both Gondwana and Laurasia as early as the earliest Cretaceous, perhaps the Late Jurassic. This history has been more complex than the classical one reconstructed in the context of a dual world (Gondwana vs. Laurasia). Geological and paleobiogeographical data show that Africa was isolated from the Mid-Cretaceous (Albian-Aptian) to Early Miocene, i.e., for ca. 75 million years. The isolation of Africa was broken intermittently by discontinuous filter routes that linked it to some other Gondwanan continents (Madagascar, South America, and perhaps India), but mainly to Laurasia. Interchanges with Gondwana were rare and mainly "out-of-Africa" dispersals, whereas interchanges with Laurasia were numerous and bidirectional, although mainly from Laurasia to Africa. Despite these intermittent connections, isolation resulted in remarkable absences, poor diversity, and emergence of endemic taxa in Africa. Mammals suggest that an African faunal province might have appeared by Late Jurassic or earliest Cretaceous times, i.e., before the opening of the South Atlantic. During isolation, Africa was inhabited by vicariant West Gondwanan taxa (i.e., taxa inherited from the former South American-African block) that represent the African autochthonous forms, and by immigrants that entered Africa owing to filter routes. Nearly all, or all immigrants were of Laurasian origin. Trans-Tethyan dispersals between Africa and Laurasia were relatively frequent during the Cretaceous and Paleogene and are documented as early as the earliest Cretaceous or perhaps Late Jurassic, i.e., perhaps by the time of completion of the Tethys between Gondwana and Laurasia. They were permitted by the Mediterranean Tethyan Sill, a discontinuous route that connected Africa to Laurasia and was controlled by sea-level changes. Interchanges fi
Keywords: African Research